Common Attractive Points Theorems of Some Generalized Hybrid Mappings in Hilbert Spaces - Panadda Thongpaen (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
In this thesis, we study an existence theorem and convergence theorems for common attractive points of widely more generalized hybrid mappings in real Hilbert spaces. We also use the Ishikawa iteration to prove weak convergence theorems for common attrac- tive points of some generalized hybrid mappings without assuming the closedness of the domain. Moreover, our main result can be apply to common xed point theorems for such mappings.